Management of routine and periodic maintenance for highway pavements - Dissanayake, Dilum Deepika; Fujiwara, Okitsugu; Morisugi, Hisa; Nagarur, Nagendra N.; Government of Japan (Bangkok : Asian Institute of Technology, 1997)
Maintenance management of highway pavements is challenging due to the randomness appears in the process of deterioration. Investment on pavement maintenance is considered as a key factor for the acceptable level of service whereas the highway agencies are always constrained by the budget allocated to them. An attempt is made to find out the optimal maintenance decisions for highway management system by utilizing the available budget in order to maximize the net benefits considered in terms of the savings of vehicle operating costs due to the application of various maintenance alternatives. Main optimization model is formulated using Probabilistic Dynamic Programming (PDP) in conjunction with Markov process due to the probabilistic nature of pavement condition and later converted to a Linear Programming (LP) model based on the maximization of expected long-run average net benefits. A numerical analysis using flexible road pavement data from the Chachoeng Sao highway division in Thailand was carried out to verify the formulated LP model.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1997
Keywords: Pavements -- Maintenance and repair